MODIFIED METHOD AND DESIGN OF A POWER BRAKE STAND FOR VEHICLE TESTING - Igor M. Blyankinstein; Pavel M. Tarasov (International Journal of Advanced Studies, 2022)
The principles of functioning of stands for testing the braking qualities of wheeled vehicles are considered. Their advantages and disadvantages are analyzed. There is a general disadvantage of the most common power brake roller stands in practice – the difference in the shape of the contact spot and the acting forces and reactions of the wheel on the support rollers and in road conditions. As a result of the system analysis of structures, a modified method and design of a power roller stand with an original support device in the form of a horizontally rotating disk are proposed. The description of the principle of implementation of tests on braking qualities and suspension of vehicles is given.